Silencing NEDD4L Effectively Inhibits the Malignant Behaviors of Hepatocellular Carcinoma - Dai J; Zhu T; Wan J; Liu R; Song Y; Zhang D; Wang X; Zhang H; Li W; Lin J; Zhu X; Liu Y (Journal of Hepatocellular Carcinoma)
Junze Dai,1,2,* Tong Zhu,3,* Jun Wan,4,* Ruibin Liu,5 Yuxuan Song,5 Dingye Zhang,5 Xin Wang,5 Huiyu Zhang,5 Wenxin Li,2,* Jie Lin,5 Xudong Zhu,5,6 Yefu Liu2,6 1Graduate School, Dalian Medical University, Dalian, Liaoning, 116044, People’s Republic of China; 2Department of Hepatopancreatobiliary Surgery, Cancer Hospital of China Medical University, Liaoning Cancer Hospital & Institute, Shenyang, Liaoning, 110042, People’s Republic of China; 3Department of Breast Surgery, Panjin Central Hospital, Panjin, 124010, People’s Republic of China; 4Second General Surgery Department, Central Hospital of Shenyang Sujiatun, Shenyang, Liaoning, 110101, People’s Republic of China; 5Department of General Surgery, Cancer Hospital of Dalian University of Technology, Cancer Hospital of China Medical University, Liaoning Cancer Hospital & Institute, Shenyang, Liaoning, 110042, People’s Republic of China; 6Liaoning Provincial Key Laboratory of Precision Medicine for Malignant Tumors, Shenyang, Liaoning, 110042, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xudong Zhu, Department of General Surgery, Cancer Hospital of Dalian University of Technology, Cancer Hospital of China Medical University, Liaoning Cancer Hospital & Institute, Shenyang, Liaoning, 110042, People’s Republic of China, Email xdzhu@cmu.edu.cn Yefu Liu, Department of Hepatopancreatobiliary Surgery, Cancer Hospital of China Medical University, Liaoning Cancer Hospital & Institute, No. 44 Xiaoheyan Road, Dadong District, Shenyang, Liaoning, 110042, People’s Republic of China, Email 97902153@cmu.edu.cnBackground: NEDD4L, an E3 ubiquitin ligase, has served a pivotal function in the malignant progression of different cancers. However, research focusing on its involvement in hepatocellular carcinoma (HCC) remains relatively scarce.Methods: This investigation examined NEDD4L’s expression, survival implications, and regulatory mechanisms of NEDD4L in HCC using RNA-seq and microarray data across multiple databases. Additionally, we investigated the impact of NEDD4L expression on malignant biological behaviors of HCC by in vitro functional assays including Edu, CCK-8, Transwell, and wound healing assay. Finally, single-cell sequencing data from HCC patients were employed to further investigate and validate NEDD4L expression patterns across various stages of HCC and its immune functional states.Results: NEDD4L was identified as one of the most markedly differentially expressed genes linked to ubiquitination in HCC and was noted to be an independent prognostic marker for overall survival, with higher expression levels correlating with poorer outcomes. Knockdown of NEDD4L significantly inhibited cell proliferation, migration, and scratch healing ability in HCC. Moreover, NEDD4L expression was closely linked to the regulation of the cell cycle and DNA damage repair, potentially driving abnormal cell cycle progression and HCC development by mediating the degradation of inhibitory cell cycle checkpoints or their upstream transcription factors via ubiquitination. Single-cell sequencing analysis revealed that NEDD4L was notably enriched in cancer stem cell populations across different HCC developmental stages and immune states, with subgroups exhibiting high NEDD4L expression sharing substantial co-expressed genes with stem cell subpopulations. Furthermore, an analysis of NEDD4L’s relationships with immune infiltration indicated that NEDD4L could facilitate immune evasion in HCC by downregulating stimulatory immune checkpoints and immune cell infiltration, a phenomenon also observed in other types of tumors.Conclusion: These findings indicate that NEDD4L is upregulated in HCC and strongly associated with unfavorable patient outcomes, pointing to its prospective utility as a biomarker for HCC. Furthermore, silencing NEDD4L could effectively inhibit the malignant behaviors of HCC. Given its dual role in regulating both cell cycle and immune checkpoints, NEDD4L represents a promising therapeutic target for HCC. Targeting NEDD4L could potentially enhance the efficacy of cyclin-dependent kinase inhibitors and immune checkpoint inhibitors.Keywords: hepatocellular carcinoma, immune suppression, NEDD4L, therapeutic target